Products Of Primitive Roots Of Unity

Algebra Level 4

Let ζ m \zeta_m be a primitive m th m^\text{th} root of unity, and
let ζ n \zeta_n be a primitive n th n^\text{th} root of unity.
Then ζ m ζ n \zeta_m\zeta_n is a primitive th \ell^\text{th} root of unity for some positive integer . \ell.

What can we say about \ell in general?


Clarification: In the answer choices, gcd ( ) \gcd(\cdot) and lcm ( ) \text{lcm}(\cdot) denote the greatest common divisor function and the lowest common multiple function, respectively.

= m n \ell = mn = gcd ( m , n ) \ell = \gcd(m,n) = lcm ( m , n ) \ell = \text{lcm}(m,n) None of these choices

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Relevant wiki: Primitive Roots of Unity

Let ζ m = e 2 π k 1 i m , ζ n = e 2 π k 2 i n , ζ l = e 2 π k 3 i l \large \zeta_{m}=e^{\frac{2\pi k_1i}{m}},\zeta_{n}=e^{\frac{2\pi k_2i}{n}},\zeta_{l}=e^{\frac{2\pi k_3i}{l}}

As per conditions we have ζ m ζ n = ζ l k 1 m + k 2 n = k 3 l \zeta_{m}\zeta_{n}=\zeta_{l}\implies \frac{k_1}{m}+\frac{k_2}{n}=\frac{k_3}{l} .

Moreover Since it's a primitive root of unity \text{primitive root of unity} , We have ( k 1 , m ) = ( k 2 , n ) = ( k 3 , l ) = 1 (k_1,m)=(k_2,n)=(k_3,l)=1 where k 1 [ 1 , m ] , k 2 [ 1 , n ] , k 3 [ 1 , l ] k_1\in[1,m],k_2\in[1,n],k_3\in[1,l]

Case 1: \text{Case 1:} Suppose l = g c d ( m , n ) g c d ( m l , n l = 1 ) l=gcd(m,n)\implies gcd(\frac{m}{l},\frac{n}{l}=1) , ( k 1 , m ) = 1 ( k 1 , m l ) = 1 (k_1,m)=1\implies (k_1,\frac{m}{l})=1 . Similarly ( k 2 , n l ) = 1 (k_2,\frac{n}{l})=1 .

So k 1 m l + k 2 n l = k 3 \large \frac{k_1}{\frac{m}{l}} + \frac{k_2}{\frac{n}{l}} = k_3 , RHS is an integer but LHS is irreducible since ( k 1 , m l ) = 1 , ( k 2 , n l ) = 1 (k_1,\frac{m}{l})=1,(k_2,\frac{n}{l})=1 . Case Dismissed \text{Case Dismissed}

Case 2: \text{Case 2:} Suppose l = m n l=mn . So we have the following facts :

{ ( k 3 , l ) = 1 ( k 3 , m n ) = 1 ( k 3 , m ) = 1 ( k 3 , n ) = 1 \begin{cases} (k_3,l)=1 \\ (k_3,mn)=1 \\ (k_3,m)=1 \\(k_3,n)=1\end{cases}

Putting l = m n l=mn we get , k 1 n k 3 + k 2 m k 3 = 1 \frac{k_1n}{k_3}+\frac{k_2m}{k_3}=1 . So k 3 k 1 , k 2 k_3|k_1,k_2 which is a special requirement for this identity to be satisfied and not always true. So Case Dismissed \text{Case Dismissed}

Case 3 : \text{Case 3 :} Suppose l = l c m ( m , n ) , l = m x = n y l=lcm(m,n), l=mx=ny with ( x , y ) = 1 (x,y)=1 , ( k 3 , m x ) = ( k 3 , n y ) = 1 ( k 3 , m ) = ( k 3 , x ) = ( k 3 , n ) = ( k 3 , y ) = 1 (k_3,mx)=(k_3,ny)=1\implies (k_3,m)=(k_3,x)=(k_3,n)=(k_3,y)=1 . So we get putting m = l x , n = l y m=\frac{l}{x},n=\frac{l}{y} ,

k 1 x + k 2 y = k 3 k 1 x k 3 + k 2 y k 3 = 1 k_1x+k_2y=k_3\implies k_1\frac{x}{k_3} + k_2\frac{y}{k_3}=1 . Again since RHS is an integer we must have LHS integer.

So, k 3 k 1 , k 2 k_3|k_1,k_2 which is the requirement for l = l c m ( m , n ) l=lcm(m,n) to be true. So in general we can't say this is always true. Case Dismissed \text{Case Dismissed}

So none of the options fit so we have, None Of These \text{So none of the options fit so we have, None Of These}

This is nice, but it is more than is necessary to solve the problem. It's enough to give a counterexample: e.g. m = 6 , n = 10 m=6,n=10 leads to = 15 , \ell = 15, which is none of the three possibilities.

Patrick Corn - 5 years, 1 month ago

Log in to reply

Yes ofcourse, you are right. But in case we need to prove it a general solution is what I gave.

Aditya Narayan Sharma - 5 years, 1 month ago
Mark Hennings
May 18, 2016

An even easier counterexample comes from m = n = 2 m=n=2 and = 1 \ell=1 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...